Ionic Composition and Driving Factors of Salt Lake Brines in the Burabay Massif, Eastern Kazakhstan - Agaliyeva, Bakytgul; Mataibayeva, Indira; Amralinova, Bakytzhan; Frolova, Olga; Mussakanova, Sayash (Engineering, Technology & Applied Science Research, 2026)
The salt lakes of the Burabay massif in Eastern Kazakhstan form unique geochemical systems shaped by a sharply continental climate, where evaporation exceeds precipitation. The hydrochemical analyses of 15 lakes showed mineralization ranging from 529 to 9023 mg/L and alkaline pH values between 8.1 and 9.3. The ionic composition is dominated by sodium, bicarbonate, chloride, and sulfate, reflecting a progressive evolution from Ca–HCO3 waters in young lakes to highly mineralized Na–Cl and Na–CO3 brines in closed basins. Geochemical modeling using Saturation Indices (SIs) (PHREEQC) indicates supersaturation with calcite, dolomite, and sodium carbonate in most lakes, while gypsum remains undersaturated and halite is near equilibrium in highly saline environments. This evidence points to active carbonate precipitation, evaporation-driven concentration, and the formation of soda-type waters. The analysis regarding Rare Earth Elements (REE) revealed positive correlations between mineralization, alkaline conditions, and REE accumulation in both water and bottom sediments, highlighting Burabay lakes as natural laboratories for studying evaporative concentration, hydrochemical evolution, and geochemical behavior of trace elements in arid continental settings.